ANALISIS PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), NET PROFIT MARGIN (NPM), DAN FIRM SIZE TERHADAP EARNING PER SHARE (EPS) (Studi pada Perusahaan Sektor Industri Dasar dan Kimia yang tercatat di BEI Periode 2014-2018) - Muhammad Subhan Nurul Umam; Edi Wijayanto; Mochammad Abdul Kodir (KEUNIS, 2019)
The purpose of this research is to analyze the effect and significancy of current ratio, debt to equity ratio, net profit margin, and firm size toward earning per share at Basic Industry And Chemicals Sector Companies during the period 2014-2018. The population and sample in this research is 7 companies at the Basic Industry And Chemicals Sector Companies which is chosen by proposive sampling. Analyze model used in this research is multiple linear regression dated panel analysis model operated by the software eviews 10.0. The result of the multiple linear regression analysis dated panel model shows that (1) The current ratio toward earning per share is not significant (2) The effect debt to equity ratio toward earning per share is not significant (3) The effect of net profit margin toward earning per share is significant (4) The effect of firm size toward earning per share is significant.